Pengaruh Ekstrak Berbagai Bagian Dari Tanaman Swietenia mahagoni Terhadap Perkecambahan Benih Kacang Hijau Dan Jagung - Stela Wusono; John M Matinahoru; CMA Watimena (Agrologia, 2015)
Swietenia mahagoni is a timber forestry plants have allelopathy toxic, can interfere with the growth of surrounding plants. This study aimed to determine the effects of extracts from various parts of Swietenia mahagoni on seed germination of green beans and corn. This research was conducted at the Laboratory of Silviculture, an extract from a litter, fresh leaves, bark and roots of the Swietenia mahagoni plant and given to the seed germination green beans and corn. The results showed that the extract of fresh leaves and roots Swietenia mahagoni inhibit seed germination green beans and corn, while the provision of litter no effect. Green bean seed has a higher durability of the maize seed to allelopathy of root Swietenia mahagoni.